Effect of School Leadership Programs on Educational Outcomes vis-a-vis SDGs: A comparative study of Nepal and its selected neighbors - Pant, Yashodhara Joshi (Innovative Research Journal, 2023)
Effective school leadership is crucial for creating a positive school environment to improve teacher performance and enhance student outcomes. This article highlights the importance of prioritizing school leadership development and investing in training and support for school leaders in Nepal and its selected neighbors. It also establishes a theoretical link between school leadership development and achieving SDGs in education. The methodology used for this study was secondary data analysis of the literature from various sources, such as research papers, reports, and other relevant documents. The article attempts to contribute to the body of knowledge on school leadership development providing useful insights for policymakers and educators to improve educational outcomes.